Non-enzymatic glycosylation of collagen and its relation to glycosylated haemoglobin in acute short-term diabetes - (:unkn) unknown (My University, 1990)
Non-enzymatic glycosylation of collagen from rat-tail tendon was measured using the thiobarbitüric acid method in both normal and diabetic rats. Results were correlated with the glycosylated haemoglobin values. The non-enzymatic glycosylation of collagen increased in diabetics and showed a weak correlation with glycosylated haemoglobin (r = 0.735). Our findings showed that acute short-term diabetes can also cause an increase in non-enzymatic glycosylation of collagen and haemoglobin.
Keywords: Female; Animals; Collagen; Glycosylation; Rats; Regression Analysis; Glucose; Diabetes Mellitus, Experimental; Acute Disease; Rats, Inbred Strains; Hemoglobins